A phase1 study of stereotactic gene delivery of AAV2‐NGF for Alzheimer's disease. Issue 5 (9th January 2014) - Rafii, Michael S.; Baumann, Tiffany L.; Bakay, Roy A. E.; Ostrove, Jeffrey M.; Siffert, Joao; Fleisher, Adam S.; Herzog, Christopher D.; Barba, David; Pay, Mary; Salmon, David P.; Chu, Yaping; Kordower, Jeffrey H.; et al.
Abstract: Background: Nerve growth factor (NGF) is an endogenous neurotrophic‐factor protein with the potential to restore function and to protect degenerating cholinergic neurons in Alzheimer's disease (AD), but safe and effective delivery has proved unsuccessful. Methods: Gene transfer, combined with stereotactic surgery, offers a potential means to solve the long‐standing delivery obstacles. An open‐label clinical trial evaluated the safety and tolerability, and initial efficacy of three ascending doses of the genetically engineered gene‐therapy vector adeno‐associated virus serotype 2 delivering NGF (AAV2‐NGF [CERE‐110]). Ten subjects with AD received bilateral AAV2‐NGF stereotactically into the nucleus basalis of Meynert. Results: AAV2‐NGF was safe and well‐tolerated for 2 years. Positron emission tomographic imaging and neuropsychological testing showed no evidence of accelerated decline. Brain autopsy tissue confirmed long‐term, targeted, gene‐mediated NGF expression and bioactivity. Conclusions: This trial provides important evidence that bilateral stereotactic administration of AAV2‐NGF to the nucleus basalis of Meynert is feasible, well‐tolerated, and able to produce long‐term, biologically active NGF expression, supporting the initiation of an ongoing multicenter, double‐blind, sham‐surgery‐controlled trial.